The Effect of Therapeutic Group Therapy and Token Economy Therapy to Preschool-Age Developmental Task of Preschool Age Children in Kelurahan Campaka Bandung West Java - Ricky, Denny Paul (Journal of International Scholars Conference - ALLIED HEALTH, 2016)
Child stimulation development services in Campaka District was not available yet. The aims of this research is to know the effect of therapeutic group therapy and token economy to developmental aspects and developmental task of preschoolers: initiative. This research uses quasi-experimental with control group. Respondents in this study were 50 pairs of mother and school-age children which is taken using consecutive sampling technique. There were 24 pairs who received therapeutic group therapy and token economy and 26 pairs who did not receive therapy. Independent t-test and paired t-test were used for analysis. The result showed developmental aspects and developmental of initiative in preschoolerswas significantly higher in the group receiving therapeutic group therapy and token economy than the group who did not receive therapy(p-value < 0.05). Developmental aspects has a significant relationship to development of initiative in preschoolers. Therapeutic group therapy and token economy can be one therapeutic option to improve develompental aspects and developmental task of preschoolers.